Building a C-P bond to unlock the reversible and fast lithium storage performance of black phosphorus in all-solid-state lithium-ion batteries. (June 2021) - Yang, J.; Mo, F.; Huang, L.; Liang, H.; Sun, G.; Peng, S.
Abstract: Black phosphorus/natural graphene (BP/NG) composite electrode material for all-solid-state lithium-ion batteries (ASSLIBs) was fabricated by a facile ball milling method. A C-P bond with characteristics of high ion and electron transfer was constructed, which unlocked the reversible cycling and rate performance of phosphorus. In addition, compounding black phosphorus (BP) with natural graphene (NG) can relieve the large internal stress caused by volume change during cycling and improve the stability of the long cycling and high-rate performance. At current density of 0.5 A g −1, a high specific capacity of 750 mAh g −1 remained after 100 cycles, whereas at high current density of 1 A g −1, the BP/NG anode material delivered a reversible capacity of 300 mAh g −1 . Furthermore, the reaction controlling step of Li x P delithiation was revealed by kinetic measurement. In addition, when coupling BP/NG anode material with TiS2 to assemble a full solid-state cell, it delivered a high capacity of 400 mAh g −1 after 30 cycles, indicating a potential of further application. This work expanded the candidate of anode materials for ASSLIBs and provided aid for the further application of all-solid-state batteries. Graphical abstract: Image 1 Highlights: A C-P bond in black phosphorus/natural graphene (BP/NG) was built by a facile ball milling method. The reversible and fast all-solid lithium storage performance of BP/NG was unlocked. A solid-state full cell with stable cycling performance was assembled using BP/NG anode.